Progressive macular hypomelanosis among Egyptian patients: a clinicopathological study - Mohamed Khaled Selim (Mattioli1885, 2011)
Background: Progressive macular hypomelanosis (PMH) is a disease of unclear etiology. Propionbacterium acnes (P. acnes) was claimed to be an etiological factor.